Unveiling the Role of Learning Motivation and Language Attitudes in Enhancing English Proficiency Among Non-English Major Students: English - siti masluha (Prodi Tadris Bahasa Inggris, 2025)
With language attitudes as a mediating factor, this study looks at how learning motivation affects the English language proficiency of non-English major students at Panca Marga University. Data were gathered by means of structured questionnaires and examined using Smart PLS from a sample of one hundred students from the Faculty of Economics and Business chosen by accident sampling. The results show that language attitudes and English proficiency are much improved by learning motivation, defined by interest levels, learning goals, and effort. Interest levels refer to the students' genuine curiosity and enthusiasm for learning English, learning goals are the specific objectives they set for themselves in mastering the language, and effort reflects the amount of time and energy they dedicate to their studies to achieve proficiency. Moreover, good language attitudes—that is, favorable impressions, curiosity, and appreciation of English's usefulness—directly increase speaking, listening, reading, and writing ability. Especially, language attitudes show their cooperative influence on language acquisition and help to moderate the relationship between motivation and proficiency. These findings highlight the need of encouraging drive and developing good attitudes to enable good English proficiency. This study helps to create focused plans for raising language proficiency in non-English academic environments.